(untitled) (Bangladesh Journal of Livestock Research, 2020)
The study was conducted to determine fodder production, estimated profitability of fodder farmers and constrains to its production.In this regard, four study areas were selected from four districts viz: Dinajpur,Jessore, Kurigram andRangpur purposively considering the concentration of fodder production. A purposive sampling technique was followed for collecting primary data from the field. Two categories of sample farmerswere selected namely: i) Fodder Producer cum seller (FPS); ii) Fodder Producer cum Dairy owner (FPDO) having 1-2 dairy cows as small, 3-4 dairy cows as medium and 5 and above dairy cows as large farmer.A total of 160 fodder farmers were interviewed. Field survey method and focus group discussions were followed to collectnecessary data and information. Descriptive statistics were applied to meet the objectives and to get the desirable outputs.The study revealed that99 per cent FPS cultivatednapier (Pennisetumpur-pureum), whereas fodder producer cultivated90 per cent. The ratio of land under fodder production and farm size was 0.10 and 0.29 for producer and FPS, respectively. In case of cattle holdings, fodder farmers reared more cross-bred cattle than the local cattle. The highest numbercross-bred cattle (22.95/ farm) were reared by producer in Dinajpur district,whereas FPSreared 9.88 cattle per farm in Jessore district.The production cost of fodder for producer was estimated the highest (Tk 1,87,598/ha) in Kurigram district and the lowest (Tk 1,71,883/ha) for FPS in Kurigram district. The bio-mass yield was the highest (214.05 t/ha) for producer in Dinajpur district and the lowest was (201.45 t/ha) for FPS in kurigram district. Annual net return from fodder production was estimated the highest (Tk 2,12,272/ha) for FPS in Jessore district and the lowest (Tk 1,29,806/ha) for FPS in Kurigram district. The BCR was the highest 2.18 for FPS in Jessore district and the lowest was 1.75 for FPS in Kurigram district. Problems faced by the fodder farmers were lack of HYV fodder species, lack of knowledge, and lack of input facilities. The study suggested supply of HYV fodder, provide training on fodder cultivation and preservation, availability of more milk producing cattle breed in fodder production areas. Bangladesh J. of Livestock Res. 20(1-2): 54-67, Jan-Dec 2013